A descriptive study of the use of events as a communication tools by non-profit organizations, inclusive of the management of an event for Hi! Theatre. - Lee, Michele Siew Fern. (2008)
The objectives for this study are to understand how non-profit organisations use events to communicate to their publics, to assess the effectiveness of events and to make recommendations.